Green flame-retardant UV (ultraviolet) curing adhesive and preparation method thereof
By combining polyurethane acrylate resin and epoxy acrylate resin, combined with nitrogen-phosphorus composite flame retardant and specific reinforcement materials, a green flame retardant UV ultraviolet curing adhesive was prepared, which solved the problems of insufficient bonding strength and low flame retardant performance of existing adhesives in harsh environments, and achieved high hardness, fast curing, good flame retardant and high adhesion effects.
Patent Information
- Application Number
- CN202510190861.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-29
AI Technical Summary
The existing UV light curing glue lacks bonding strength and durability under harsh environmental conditions, and has low flame retardant performance, which cannot meet the application needs of radio frequency antenna screw fixing of communication base stations.
A green flame retardant UV ultraviolet curing glue is prepared by combining polyurethane acrylate resin and epoxy acrylate resin, combined with 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide and diethanolamine, as well as specific organic-inorganic reinforcement materials and acrylate monomers.
It achieves fast curing, high hardness, flame retardant reaching UL94V-0 level, can withstand excessive hot and cold shocks and has good adhesion to aluminum, and meets the application needs of radio frequency antenna screw fixing of communication base stations.
Smart Images

Figure BDA0005279960860000121 
Figure BDA0005279960860000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a green flame-retardant UV ultraviolet light-curing adhesive and a preparation method thereof. Background Art
[0002] With the development of modern communication technology, especially the accelerated pace of 5G network construction, the requirements for communication base station equipment are getting higher and higher. As one of the important components of the base station, the reliability and safety of the RF antenna during its installation and maintenance are particularly important. Traditional fixing methods mostly use mechanical fasteners such as screws. However, under harsh environmental conditions (such as high temperature, low temperature, humidity, etc.), traditional adhesives often cannot provide sufficient bonding strength and durability, and are prone to aging, falling off and other problems, affecting the stable operation of the system.
[0003] In addition, considering safety factors, especially when used in confined spaces or outdoor environments, the flame retardant performance of the material becomes an indispensable key indicator. Although there are many types of UV light-curing adhesives on the market, they generally have disadvantages such as long curing time, insufficient hardness, low flame retardant grade and poor adhesion to metal substrates, which cannot fully meet the needs of the above application scenarios.
[0004] Therefore, in response to the needs of application fields such as screw fixing on radio frequency antennas of communication base stations, it is of great significance to develop a green flame retardant UV ultraviolet light curing adhesive with fast curing, high hardness, flame retardant UL94V-0 level, ability to withstand excessive cold and heat shock and good adhesion to aluminum, which is of great significance for improving production efficiency, ensuring equipment safety and extending service life. Summary of the invention
[0005] The purpose of the present invention is to provide a green flame-retardant UV ultraviolet light-curing adhesive and a preparation method thereof. The green flame-retardant UV ultraviolet light-curing adhesive not only has fast curing, high hardness, and flame retardancy that can reach UL94V-0 level, but also can withstand thermal shock and has good adhesion to aluminum, and can meet the needs of application fields such as screw fixing on radio frequency antennas of communication base stations.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A green flame-retardant UV ultraviolet light curing adhesive. The raw materials for its preparation include, by weight, 40-60 parts of a resin matrix, 5-15 parts of an acrylate monomer, 1-3 parts of a photoinitiator, 2-5 parts of an adhesion promoter, and 10-20 parts of a flame retardant.
[0008] Preferably, the resin matrix includes flame retardant polyurethane acrylate resin or flame retardant epoxy acrylate resin.
[0009] Preferably, the mass ratio of the flame retardant polyurethane acrylate resin to the flame retardant epoxy acrylate resin is 1:(0.5-2); further preferably, it is 1:1.
[0010] The method for preparing the flame retardant polyurethane acrylate resin comprises the following steps:
[0011] S1. Dissolve 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in tetrahydrofuran, add maleic anhydride, stir and react at 40-50° C. for 7-9 hours, and then dry in vacuum until constant weight to obtain substance 1;
[0012] S2, taking the material monoethanolamine, diethanolamine, catalyst and toluene, mixing them, stirring and reacting at 100-110°C for 7-9h, cooling to 80-90°C and drying under vacuum to constant weight, thus obtaining a nitrogen-phosphorus composite flame retardant;
[0013] S3. Mix polytetramethylene glycol and a crosslinking agent, raise the temperature to 40-50°C, drop hexamethylene diisocyanate, raise the temperature to 50-60°C and react until the -NCO content reaches half of the initial content and remains unchanged, add a nitrogen-phosphorus composite flame retardant, raise the temperature to 75-80°C and react for 0.5-1h, then cool to 65-70°C, add hydroxyethyl methacrylate and dibutyltin dilaurate, react for 0.5h, detect the -NCO content in the system, and stop the reaction if the -NCO content is less than 0.3%. Cool the material to obtain a flame-retardant polyurethane acrylate resin.
[0014] The preparation of photocurable adhesive by compounding polyurethane acrylic resin and epoxy acrylic resin can not only make the photocurable adhesive have a faster curing speed and higher hardness, but also improve its resistance to cold and hot shocks and flexibility, and improve its adhesion. This may be because polyurethane acrylic resin and epoxy acrylic resin can form an interpenetrating polymer network structure during the photocuring process, so that the two resins can penetrate and interweave with each other after curing, thereby forming a photocurable adhesive with better overall performance. Polyurethane acrylic resin itself has excellent flexibility and high temperature resistance, and the use of polytetramethylene diisocyanate and hexamethylene diisocyanate as soft segments and hard segments respectively further improves the flexibility and impact resistance of the prepared polyurethane acrylic resin, and can improve the wettability with the metal substrate, which helps the coating to fit the metal surface more closely, so that the amino esters contained in the main chain can form a large number of hydrogen bonds with the substrate surface, thereby improving the adhesion with the metal substrate. However, the effect of improving the overall performance of the photocurable adhesive is limited. By compounding a specific bisphenol A epoxy acrylate resin, the rigid bisphenol A unit and polar functional groups in the molecule not only give the photocuring adhesive a higher hardness, but also improve the interaction between the photocuring adhesive and the metal substrate, thereby improving the adhesion. However, the epoxy acrylate resin still has a certain internal stress after curing, which makes the adhesion low. This defect can be compensated by compounding with polyurethane acrylate.
[0015] Preferably, the molar ratio of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to maleic anhydride is 1:(1-1.2).
[0016] Preferably, the mass ratio of the substance 1 to diethanolamine is (2.5-3.5):1.
[0017] Preferably, the catalyst is p-toluenesulfonic acid, and the added amount is 1% of the total mass of substance 1 and diethanolamine.
[0018] Preferably, the relative molecular weight of the polytetramethylene ether diol is 1800-2000, and the viscosity at 40° C. is 1215-1225 cp.
[0019] In some preferred embodiments, the polytetrahydrofuran ether diol is purchased from Jinan Guangyu Chemical Co., Ltd.
[0020] Preferably, the mass ratio of the polytetramethylene ether diol, hexamethylene diisocyanate and hydroxyethyl methacrylate is (6-8):(2-2.5):1.
[0021] Preferably, the crosslinking agent is 1,6-hexanediol diacrylate, and the added amount is 2%-10% of the mass of polytetramethylene ether diol.
[0022] Preferably, the added amount of the nitrogen-phosphorus composite flame retardant is 5%-10% of the total mass of polytetramethylene ether diol and hexamethylene diisocyanate.
[0023] Preferably, the added amount of the dibutyltin dilaurate is 0.1%-0.3% of the total mass of the polytetramethylene ether glycol and hexamethylene diisocyanate.
[0024] Although the added flame retardant has a certain flame retardant effect, it has poor compatibility with the polyurethane acrylate resin, which will affect the structural stability of the polyurethane acrylate resin and thus affect the performance of the photocurable adhesive. In order to improve the flame retardancy of the photocurable adhesive while ensuring the various properties of the photocurable adhesive, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and diethanolamine were used to synthesize a nitrogen-phosphorus composite flame retardant, and it was used to prepare polyurethane, which can improve the flame retardancy of the photocurable adhesive without affecting the stability of polyurethane acrylate. This may be because by grafting maleic anhydride on the phosphorus-containing flame retardant 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, the activity of the prepared substance 1 is improved, so that diethanolamine can react smoothly with it and generate a nitrogen-phosphorus composite flame retardant containing hydroxyl groups, so that the flame retardant can be used as a chain extender in the preparation of polyurethane acrylate resin, which can not only improve the flame retardancy and thermal stability of the photocurable adhesive finally prepared, but also will not affect its impact resistance, hardness and other properties. However, when synthesizing polyurethane acrylate, the addition of nitrogen-phosphorus composite flame retardant as a chain extender is limited, and the addition of epoxy acrylate resin will reduce the flame retardancy of the system. Therefore, certain flame retardants must also be added to the epoxy acrylate resin to ensure the flame retardant effect of the photocuring adhesive.
[0025] The preparation method of the flame retardant epoxy acrylic resin comprises the following steps: mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and epoxy acrylic resin, mixing for 10-20 minutes at 110-120° C. under nitrogen protection, cooling to 80-90° C., adding organic-inorganic reinforcing material, and ultrasonically dispersing for 1-2 hours at a power of 150-250 W to obtain the flame retardant epoxy acrylic resin.
[0026] Preferably, the epoxy acrylic resin is bisphenol A epoxy acrylic resin, with an acid value of ≤5 mg KOH / g, a viscosity of 3300-5000 mPa·s at 65.5° C., and a functionality of 2.
[0027] In some preferred embodiments, the epoxy acrylic resin is purchased from Allnex, Ebecryl3701.
[0028] Preferably, the addition amount of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 3%-5% of the mass of the epoxy acrylic resin.
[0029] Preferably, the organic-inorganic reinforcing material includes γ-glycidyl ether silylpropyl sesquioxane and dodecyl-cage polysilsesquioxane.
[0030] Preferably, the mass ratio of the γ-glycidyl ether silylpropyl sesquioxane to the dodecyl-cage polysilsesquioxane is 1:(0.8-1.2); more preferably, it is 1:1.
[0031] Preferably, the addition amount of the organic-inorganic reinforcing material is 5%-10% of the total mass of the epoxy acrylic resin.
[0032] If a flame retardant containing phosphorus groups is introduced into epoxy acrylate resin, the thermal stability and mechanical properties of epoxy resin will be affected, and then the performance of photocurable adhesive will be affected. By selecting specific organic-inorganic reinforcing materials, not only can the flame retardant effect of photocurable adhesive be maintained, but also the mechanical properties and thermal stability of epoxy acrylate resin can be enhanced, without negatively affecting the overall performance of photocurable adhesive. This may be because γ-glycidyl ether silyl propyl sesquioxane participates in the cross-linking reaction of the resin with its glycidyl ether functional group to form a tight network structure, while the cage structure and phenyl functional group of dodecyl-cage polysilsesquioxane increase the rigidity and wear resistance of the resin. The structural complementarity of the two enables them to support each other in the resin system and jointly improve the mechanical properties of the resin. At the same time, the high thermal stability of γ-glycidyl ether silyl propyl sesquioxane and dodecyl-cage polysilsesquioxane provides an effective thermal barrier for the resin, preventing heat transfer and thermal decomposition of the resin, and further improving the thermal stability of the resin. Moreover, γ-glycidyl ether silylpropyl sesquioxane and dodecyl-cage polysilsesquioxane also contain silicon, which can have a good flame retardant synergistic effect with the phosphorus element in 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, thereby further improving the flame retardant effect.
[0033] Preferably, the acrylate monomer is phosphate triacrylate, 2-phenoxyethyl acrylate, diethylene glycol diacrylate, or trimethylolpropane triacrylate.
[0034] Preferably, the mass ratio of the phosphoric acid triacrylate, 2-phenoxyethyl acrylate, diethylene glycol diacrylate, and trimethylolpropane triacrylate is 1:(2-4):(0.5-1.5):1.
[0035] The selection of specific acrylate monomers can not only improve the flame retardant properties of photocurable adhesives, but also optimize the mechanical properties and processing properties. This may be because triacrylate phosphate, as a phosphorus-containing monomer, not only enhances the flame retardant properties of photocurable adhesives, but also participates in the cross-linking reaction through its acrylate functional group to build a more stable network structure. 2-Phenoxyethyl acrylate optimizes the processing properties and bonding strength of photocurable adhesives with its good dilution effect and adhesion promotion properties. The addition of diethylene glycol diacrylate brings the necessary flexibility to the photocurable adhesive, enabling it to exhibit better crack resistance, impact resistance and durability when facing external forces. And trimethylolpropane triacrylate, with its high reactivity and multi-functional structure, significantly improves the photocuring speed, shortens the curing time, and enhances the wear resistance and solvent resistance of the photocurable adhesive.
[0036] Preferably, the photoinitiator includes one or more of photoinitiator 1173, photoinitiator 184, photoinitiator 907, photoinitiator TPO, photoinitiator TPO-L, photoinitiator IHT-PI 910, and photoinitiator 659; further preferably, photoinitiator 1173 and photoinitiator TPO.
[0037] Preferably, the mass ratio of the photoinitiator 1173 to the photoinitiator TPO is 1:(0.5-2); further preferably, it is 1:1.
[0038] Preferably, the adhesion promoter is an alkyl acrylate phosphate.
[0039] Preferably, the viscosity of the alkyl acrylate phosphate at room temperature is 30-80 mPa·S, and the acid value is 140-180 mgKOH / g.
[0040] In some preferred embodiments, the alkyl acrylate phosphate is purchased from Guangzhou Jingde Chemical Materials Co., Ltd.
[0041] Preferably, the flame retardant has a phosphorus content of 25%-27% and a viscosity of 1.5-3 mPa·s at 25°C.
[0042] In some preferred embodiments, the flame retardant is purchased from Suzhou Jiayi Chemical Co., Ltd., K-608.
[0043] The preparation method of the green flame-retardant UV ultraviolet light curing adhesive comprises the following steps: after the resin matrix and the acrylate monomer are evenly mixed, a photoinitiator, an adhesion promoter and a flame retardant are added, and the mixture is evenly stirred to obtain the adhesive.
[0044] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0045] 1. The present invention provides a green flame-retardant UV ultraviolet light curing adhesive, which not only has fast curing, high hardness, and flame retardancy reaching UL94V-0 level, but also can withstand thermal shock and has good adhesion to aluminum, and meets the needs of application fields such as screw fixing on radio frequency antennas of communication base stations, and is of great significance for improving production efficiency, ensuring equipment safety, and extending service life.
[0046] 2. The present invention selects polyurethane acrylic resin and epoxy acrylic resin to prepare the light-curing adhesive, which not only enables the light-curing adhesive to have a faster curing speed and higher hardness, but also improves its resistance to cold and hot shocks and flexibility, and improves its adhesion.
[0047] 3. The present invention synthesizes a nitrogen-phosphorus composite flame retardant by selecting 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and diethanolamine, and applies it to the preparation of polyurethane, which can improve the flame retardancy of the photocurable adhesive without affecting the stability of polyurethane acrylate.
[0048] 4. The present invention not only maintains the flame retardant effect of the photocuring adhesive but also enhances the mechanical properties and thermal stability of the epoxy acrylate resin by selecting specific organic-inorganic reinforcing materials, without having a negative impact on the overall performance of the photocuring adhesive.
[0049] 5. The present invention selects specific acrylate monomers, which can not only improve the flame retardant properties of the photocurable adhesive, but also optimize the mechanical properties and processing properties. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] The raw materials used in the present invention are all commercially available, specifically:
[0052] The relative molecular weight of polytetramethylene ether diol is 1800-2000, and the viscosity at 40° C. is 1215-1225 cp, and it is purchased from Jinan Guangyu Chemical Co., Ltd.
[0053] The epoxy acrylic resin is bisphenol A epoxy acrylic resin, with an acid value of ≤5 mg KOH / g, a viscosity of 3300-5000 mPa·s at 65.5° C., a functionality of 2, purchased from Allnex, Ebecryl3701.
[0054] The viscosity of the alkyl acrylate phosphate at room temperature is 30-80 mPa·S, and the acid value is 140-180 mgKOH / g. It is purchased from Guangzhou Jingde Chemical Materials Co., Ltd.
[0055] The phosphorus content of the flame retardant is 25%-27%, the viscosity at 25°C is 1.5-3mPa·s, and it is purchased from Suzhou Jiayi Chemical Co., Ltd., K-608.
[0056] Example 1
[0057] The present embodiment provides a green flame-retardant UV ultraviolet light-curing adhesive, and its preparation raw materials, by weight, are 50 parts of resin matrix, 10 parts of acrylate monomer, 2 parts of photoinitiator, 3 parts of adhesion promoter, and 15 parts of flame retardant.
[0058] The resin matrix is flame retardant polyurethane acrylate resin and flame retardant epoxy acrylate resin, and the mass ratio is 1:1.
[0059] The preparation method of the flame retardant polyurethane acrylate resin comprises the following steps:
[0060] S1. Dissolve 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in tetrahydrofuran, add maleic anhydride, stir and react at 45°C for 8h, and then dry in vacuum until constant weight to obtain substance 1;
[0061] S2, taking the material monoethanolamine, diethanolamine, catalyst and toluene, mixing them, stirring and reacting at 105°C for 8 hours, cooling to 85°C and vacuum drying to constant weight, thus obtaining a nitrogen-phosphorus composite flame retardant;
[0062] S3. Mix polytetramethylene ether diol and a cross-linking agent, heat to 45°C, drop hexamethylene diisocyanate, heat to 55°C and react until the -NCO content reaches half of the initial content and remains unchanged, add a nitrogen-phosphorus composite flame retardant, heat to 78°C and react for 1 hour, cool to 68°C, add hydroxyethyl methacrylate and dibutyltin dilaurate, react for 0.5 hour, detect the -NCO content in the system, stop the reaction if the -NCO content is less than 0.3%, cool and discharge to obtain a flame-retardant polyurethane acrylate resin.
[0063] The molar ratio of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to maleic anhydride is 1:1.2.
[0064] The mass ratio of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to tetrahydrofuran is 1:5.
[0065] The mass ratio of the substance 1 to diethanolamine is 3.2:1.
[0066] The added amount of toluene is 5 times the total mass of substance 1 and diethanolamine.
[0067] The catalyst is p-toluenesulfonic acid, and the added amount is 1% of the total mass of substance 1 and diethanolamine.
[0068] The mass ratio of the polytetramethylene ether diol, hexamethylene diisocyanate and hydroxyethyl methacrylate is 7.5:2.3:1.
[0069] The crosslinking agent is 1,6-hexanediol diacrylate, and the added amount is 6% of the mass of polytetramethylene ether diol.
[0070] The added amount of the nitrogen-phosphorus composite flame retardant is 8% of the total mass of polytetramethylene ether glycol and hexamethylene diisocyanate.
[0071] The added amount of the dibutyltin dilaurate is 0.2% of the total mass of the polytetramethylene ether glycol and hexamethylene diisocyanate.
[0072] The preparation method of the flame retardant epoxy acrylic resin comprises the following steps: mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and epoxy acrylic resin, mixing for 15 minutes at 115° C. under nitrogen protection, cooling to 85° C., adding organic-inorganic reinforcing material, and ultrasonically dispersing for 1.5 hours at a power of 200 W to obtain the flame retardant epoxy acrylic resin.
[0073] The added amount of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 4% of the mass of the epoxy acrylic resin.
[0074] The organic-inorganic reinforcing material is γ-glycidyl ether oxygen silyl propyl sesquioxane and dodecyl-cage polysilsesquioxane, and the mass ratio is 1:1.
[0075] The addition amount of the organic-inorganic reinforcing material is 8% of the total mass of the epoxy acrylic resin.
[0076] The acrylic acid ester monomers are phosphate triacrylate, 2-phenoxyethyl acrylate, diethylene glycol diacrylate, and trimethylolpropane triacrylate, and the mass ratio is 1:3:1:1.
[0077] The photoinitiators are photoinitiator 1173 and photoinitiator TPO, with a mass ratio of 1:1.
[0078] The adhesion promoter is an alkyl acrylate phosphate.
[0079] The preparation method of the green flame-retardant UV ultraviolet light curing adhesive comprises the following steps: after uniformly mixing a resin matrix and an acrylate monomer, adding a photoinitiator, an adhesion promoter and a flame retardant, and stirring uniformly to obtain the adhesive.
[0080] Example 2
[0081] The difference between this embodiment and embodiment 1 is that the mass ratio of the flame retardant polyurethane acrylate resin to the flame retardant epoxy acrylate resin is 3:2.
[0082] Comparative Example 1
[0083] The difference between this comparative example and Example 1 is that the resin matrix is a flame retardant polyurethane acrylate resin.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 1 is that the preparation method of the flame retardant polyurethane acrylate resin comprises the following steps:
[0086] S1. Dissolve 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in tetrahydrofuran, add maleic anhydride, stir and react at 45°C for 8h, and then dry in vacuum until constant weight to obtain substance 1;
[0087] S2, taking the material monoethanolamine, diethanolamine, catalyst and toluene, mixing them, stirring and reacting at 105°C for 8 hours, cooling to 85°C and vacuum drying to constant weight, thus obtaining a nitrogen-phosphorus composite flame retardant;
[0088] S3. Mix diethylene glycol adipate and a crosslinking agent, heat to 45°C, add 2,4-toluene diisocyanate dropwise, heat to 55°C and react until the -NCO content reaches half of the initial content and remains unchanged, add a nitrogen-phosphorus composite flame retardant, heat to 78°C and react for 1 hour, cool to 68°C, add hydroxyethyl methacrylate and dibutyltin dilaurate, react for 0.5 hour, detect the -NCO content in the system, stop the reaction if the -NCO content is less than 0.3%, cool and discharge to obtain a flame-retardant polyurethane acrylate resin.
[0089] The mass ratio of the polyethylene adipate, 2,4-toluene diisocyanate and hydroxyethyl methacrylate is 7.5:2.3:1.
[0090] The poly(diethylene glycol adipate) was purchased from Jining Tangyi Chemical Co., Ltd.
[0091] Comparative Example 3
[0092] The difference between this comparative example and Example 1 is that the preparation method of the flame retardant polyurethane acrylate resin comprises the following steps:
[0093] Take polytetramethylene ether diol and a crosslinking agent, mix them, heat them to 45°C, add hexamethylene diisocyanate dropwise, heat them to 55°C and react until the -NCO content reaches half of the initial content and remains unchanged, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, heat them to 78°C and react for 1 hour, then cool them to 68°C, add hydroxyethyl methacrylate and dibutyltin dilaurate, react for 0.5 hour, detect the -NCO content in the system, stop the reaction if the -NCO content is less than 0.3%, cool and discharge the material to obtain a flame retardant polyurethane acrylate resin.
[0094] The added amount of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 8% of the total mass of the polytetramethylene ether diol and hexamethylene diisocyanate.
[0095] Comparative Example 4
[0096] The difference between this comparative example and Example 1 is that the preparation method of the flame retardant epoxy acrylic resin comprises the following steps: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and epoxy acrylic resin are mixed, and the mixture is mixed at 115° C. under nitrogen protection for 15 minutes to obtain the flame retardant epoxy acrylic resin.
[0097] Comparative Example 5
[0098] The difference between this comparative example and Example 1 is that the organic-inorganic reinforcing material is γ-glycidyl ether silyl propyl sesquioxane.
[0099] Comparative Example 6
[0100] The difference between this comparative example and Example 1 is that the acrylate monomers are 2-phenoxyethyl acrylate, diethylene glycol diacrylate, and trimethylolpropane triacrylate, and the mass ratio is 3:1:1.
[0101] Performance Testing
[0102] The photocurable adhesive was coated on an aluminum plate with a thickness of 200 μm. The room temperature was about 25°C, and a 250W ultraviolet lamp was used for irradiation. The lamp distance was 4 cm and the irradiation time was 60 s. The adhesive layer was tested for adhesion according to GB / T 9286-2021, and the substrate was an aluminum plate. The impact resistance of the adhesive layer was tested according to GB / T1732-2020. Hot and cold shock strength: The photocurable adhesive was placed at -40°C and 120°C for 1 hour at each temperature. After 100 cycles, the impact resistance of the tester was tested, and the impact strength retention rate was calculated = (initial impact resistance - impact resistance after hot and cold cycles) / initial impact resistance × 100%. The film was subjected to a combustion test according to UL94 standard. The curing time was determined by the surface drying method, that is, the adhesive was applied to a glass sheet, cured under ultraviolet light, and timed with a stopwatch. When it was not sticky by finger touch, it was the surface drying time. The hardness of the adhesive layer was measured by a Shore hardness tester. The results are shown in Table 1.
[0103] Table 1 Measurement results
[0104]
[0105]
[0106] According to statistics, the green flame-retardant UV curing adhesive prepared in Examples 1 to 2 of the present invention has a short curing time, good impact resistance under hot and cold conditions, high adhesion to the aluminum base, UL94 grade reaches V-0, and has suitable hardness. In comparative example 1, no flame-retardant epoxy acrylate resin was added, in comparative example 2, polytetramethylene diisocyanate and hexamethylene diisocyanate were not selected as soft segments and hard segments, respectively, to prepare polyurethane acrylic resin, in comparative example 3, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was not synthesized, in comparative example 4, no organic-inorganic reinforcing material was added, in comparative example 5, dodecaphenyl-cage polysilsesquioxane was not added, and in comparative example 6, triacrylate phosphate was not added. The prepared green flame-retardant UV ultraviolet light-curing adhesive had poor curing time, impact resistance, adhesion, flame retardant effect, and hardness. Therefore, the green flame-retardant UV ultraviolet light-curing adhesive prepared by the raw materials and methods described in the present application not only has fast curing, high hardness, and flame retardancy that can reach UL94V-0 level, but can also withstand thermal shock and has good adhesion to aluminum, and meets the needs of application fields such as screw fixing on radio frequency antennas of communication base stations.
[0107] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A green flame retardant UV curing adhesive, characterized in that: The raw materials for its preparation include 40-60 parts of resin matrix, 5-15 parts of acrylate monomer, 1-3 parts of photoinitiator, 2-5 parts of adhesion promoter, and 10-20 parts of flame retardant by weight; The resin matrix includes a flame retardant polyurethane acrylate resin and a flame retardant epoxy acrylate resin; the preparation method of the flame retardant polyurethane acrylate resin includes the following steps: S1. Dissolve 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in tetrahydrofuran, add maleic anhydride, stir and react at 40-50° C. for 7-9 hours, and then dry in vacuum until constant weight to obtain substance 1; S2, taking the material monoethanolamine, diethanolamine, catalyst and toluene, mixing them, stirring and reacting at 100-110°C for 7-9h, cooling to 80-90°C and drying under vacuum to constant weight, thus obtaining a nitrogen-phosphorus composite flame retardant; S3. Mix polytetramethylene glycol and a crosslinking agent, raise the temperature to 40-50°C, drop hexamethylene diisocyanate, raise the temperature to 50-60°C and react until the -NCO content reaches half of the initial content and remains unchanged, add a nitrogen-phosphorus composite flame retardant, raise the temperature to 75-80°C and react for 0.5-1h, then cool to 65-70°C, add hydroxyethyl methacrylate and dibutyltin dilaurate, react for 0.5h, detect the -NCO content in the system, and stop the reaction if the -NCO content is less than 0.3%. Cool the material to obtain a flame-retardant polyurethane acrylate resin.
2. The green flame retardant UV curing adhesive according to claim 1, characterized in that: The molar ratio of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to maleic anhydride is 1:(1-1.2).
3. The green flame retardant UV curing adhesive according to claim 1, characterized in that: The mass ratio of the substance 1 to diethanolamine is (2.5-3.5):
1.
4. The green flame retardant UV curing adhesive according to claim 1, characterized in that: The relative molecular weight of the polytetramethylene ether glycol is 1800-2000, and the viscosity at 40° C. is 1215-1225 cp.
5. The green flame retardant UV curing adhesive according to claim 1, characterized in that: The mass ratio of the polytetramethylene ether diol, hexamethylene diisocyanate and hydroxyethyl methacrylate is (6-8):(2-2.5):
1.
6. The green flame retardant UV curing adhesive according to claim 1, characterized in that: The preparation method of the flame retardant epoxy acrylic resin comprises the following steps: mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and epoxy acrylic resin, mixing for 10-20 minutes at 110-120° C. under nitrogen protection, cooling to 80-90° C., adding organic-inorganic reinforcing material, and ultrasonically dispersing for 1-2 hours at a power of 150-250 W to obtain the flame retardant epoxy acrylic resin.
7. The green flame retardant UV curing adhesive according to claim 6, characterized in that: The epoxy acrylic resin is bisphenol A epoxy acrylic resin, with an acid value of ≤5 mg KOH / g, a viscosity of 3300-5000 mPa·s at 65.5° C., and a functionality of 2.
8. The method for preparing the green flame retardant UV curing adhesive according to claim 6, characterized in that: The organic-inorganic reinforcing material includes γ-glycidyl ether silylpropyl sesquioxane and dodecyl-cage polysilsesquioxane.
9. The green flame retardant UV curing adhesive according to claim 1, characterized in that: The acrylate monomers are phosphoric acid triacrylate, 2-phenoxyethyl acrylate, diethylene glycol diacrylate, and trimethylolpropane triacrylate.
10. A method for preparing the green flame retardant UV curing adhesive according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: after uniformly mixing a resin matrix and an acrylate monomer, adding a photoinitiator, an adhesion promoter and a flame retardant, and stirring the mixture uniformly to obtain the product.
Citation Information
Cited By
Phosphorus-nitrogen reactive flame retardant as well as preparation method and application thereof
CN116063353A
Hyperbranched reactive flame retardant, preparation method and rigid polyurethane foam
CN116120373A